Risk factors for multiple pregnancies in intrauterine insemination cycles with ovarian stimulation: a predictive approach - Gogineni, Kavitha; Donthu, Kiranmai; Y., Himabindu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The aim of this study was to predict the risk of multiple pregnancies during ovarian stimulation (OS) followed by intrauterine insemination (IUI) as a treatment for infertility and to identify risk factors associated with multiple pregnancies in IUI cycles. Methods: This prospective observational study was conducted on 358 couples who underwent OS with IUI between January 2022 and July 2023. Data on maternal and paternal age, type of infertility, gonadotropin dosing, follicular size, and total motile sperm concentration (TMSC) were collected. The primary outcome was clinical pregnancy, defined as the presence of a gestational sac on transvaginal ultrasound (TVS). Descriptive and regression analyses were performed to examine the relationship between these variables and the incidence of multiple pregnancies. Results: A total of 358 IUI cycles resulted in 57 clinical pregnancies, yielding a pregnancy rate of 15.9%. Among these, 87.7% were singleton pregnancies, and 12.3% were multiple pregnancies. No significant association was found between maternal age, paternal age, or type of infertility and multiple pregnancy outcomes. However, regression analysis revealed that the presence of follicles between 13-15 mm, in combination with larger follicles (>15 mm), significantly increased the likelihood of multiple pregnancies (p=0.007). Additionally, a significant relationship was found between gonadotropin dosing and multiple pregnancy rate (p<0.05), whereas TMSC did not significantly correlate with multiple pregnancy outcomes (p=0.57). Conclusions: The risk of multiple pregnancies in IUI cycles is significantly associated with follicle size, particularly the presence of follicles in the 13-15 mm range, and higher gonadotropin dosing. While TMSC did not affect multiple pregnancy rates, careful monitoring of ovarian response, especially follicle size, is crucial for minimizing the risk of multiple pregnancies and optimizing clinical outcomes in controlled OS (COS)-IUI cycles.